2014
DOI: 10.3329/bjp.v9i3.19105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of methanolic extract of <i>Malva parviflora</i> against paracetamol-induced hepatotoxicity in mice

Abstract: Malva parviflora (cheeseweed) is traditionally used as hepatoprotective. The current study was conducted to determine its hepatoprotective activity of aqueous methanolic extract of whole plant. Two doses of plant (250 and 500 mg/kg) were administered in paracetamol intoxicated mice and results were compared with silymarin. Observational parameters were ALT, AST, ALP and total bilirubin. The results showed that the extract of M. parviflora produced significant (p<0.001) reduction in liver enzymes and total bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Hepatotoxin treated group showed altered morphology and tissue necrosis while extract treated group showed fewer changes and hepatotoxicity. Phytochemical analysis of O. monacantha showed the presence of polyphenols, flavonoids, alkaloids, tannins, saponins and polysaccharides and these were reported to be hepatoprotective (Ali et al, 2013;Mallhi et al, 2014). It may be concluded that hepatoprotective activity of chloroform and methanol extract of O. monacantha is due to the presence of these important constituents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hepatotoxin treated group showed altered morphology and tissue necrosis while extract treated group showed fewer changes and hepatotoxicity. Phytochemical analysis of O. monacantha showed the presence of polyphenols, flavonoids, alkaloids, tannins, saponins and polysaccharides and these were reported to be hepatoprotective (Ali et al, 2013;Mallhi et al, 2014). It may be concluded that hepatoprotective activity of chloroform and methanol extract of O. monacantha is due to the presence of these important constituents.…”
Section: Discussionmentioning
confidence: 96%
“…The investigation of natural plants and isolation of their beneficial constituents is very vital to control liver disease (Saleem and Naseer, 2014). Many hepatoprotective plants have been identified like Cocculus hirsutus (Thakare et al, 2009), Carissa spinarum (Hegde and Joshi, 2010), Khamira Gaozaban Ambri Jadwar Ood Saleeb Wala (Akhtar et al, 2013), Trichodesma sedgwickianum (Saboo et al, 2013), Trianthema decandra (Balamurugan and Muthusamy, 2008), Convolvulus arvensis (Ali et al, 2013), Ipomoea staphylina (Bag and Mumtaz, 2013), Malva parviflora (Mallhi et al, 2014), Chenopodium murale and Rumex dentatus . Though we know the hepatoprotective and antioxidant potential of many plants, but still there is much less information available regarding the hepatoprotective potential of Opuntia monacantha commonly known as Chnutarthar from family: Cactaceae (Ahmad, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The main constituents of Conyza bonariensis are Quercetin and Kaempferol, confirmed by HPLC shown in figure 2. Both are flavonoid and reported to be hepatoprotective (Ali et al, 2013;Mallhi et al, 2014). It may be concluded that hepatoprotective activity of Conyza bonariensis is due to the presence of these important flavanoids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, significant efforts are being directed towards the searching for plant-based products that can provide efficient succor, accessibility and safer treatments (Umer et al, 2010;Mallhi et al, 2014). In addition, the search must be centered on a medicinal plant that can scavenge ROS and nitric oxide (NO), which are the intermediate products of inflammatory processes and lipid peroxidation during CCl4 mediated toxicity that eventually then added to 2.9 ml of 2% Na2CO3.…”
Section: Introductionmentioning
confidence: 99%